(untitled) (Politeja, 2022)
POLITICAL LEADERSHIP: SOME THEORETICAL ASPECTS Leadership is needed in each human community and common activity. It is most natural the area of politics, power and state. Politics is inseparably connected with leadership. Political leadership is unique power, it is a combination of leadership skills with the ability to inspire human behaviours in the social scale. Political leader has power over people as a result of their authority or by force. They can be either a democrat or a dictator. However, in all cases a political leader somebody more than ordinary politician, becoming positive or negative political giant.